Cordiais saudações: cartas e outras reflexões sobre as raízes da música popular brasileira - Henriques, Laura Luz Pessanha [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The constitution of the Brazilian people is made up by three major ethnic groups: the Indigenous, European and African, who mingled and formed what is known as the Brazilian culture. One of the most significant platform from this culture certainly is the music. In the second half of the nineteenth century and in the early twentieth, music began to be valued as national production and now is currently as diverse and significant as estimated. The book-report Best Regards: letters and other reflections on the backgrounds of Brazilian popular music makes an analysis of the reality of Brazilian popular music and its origins from experimental texts such as personal letters and fictional interviews based on actual statements about some of the most representative musicians of the early twentieth century - Assis Valente, Cartola, Chiquinha Gonzaga, Luiz Gonzaga and Noel Rosa - when the recently independent country began to establish their own particular culture. In these texts is possible, besides of knowing the biography and the pieces of these artists, compare historical contexts experienced back there with the country's current situation. The book also brings an extensive research of Brazilian's rhythms, ethnic origin, geography, as the main areas of occurrence of those rhythms in Brazil and how the dismemberment and the derivations of then, that embraces since classical music and orchestral until drumming up on the street

A formação do povo brasileiro é constituída por três grupos étnicos principais: o indígena, o europeu e o africano, que se miscigenaram e formaram o que conhecemos como a cultura brasileira. Uma das plataformas mais representativas dessa cultura é a música, que na segunda metade do século XIX e início do século XX começava a ser valorizada como produção nacional e, atualmente, é tão diversa e rica como estimada. O livro-reportagem Cordiais Saudações: Cartas e outras reflexões sobre as raízes da música popular brasileira faz uma análise sobre a realidade da música popular brasileira e das suas raízes a partir de textos experimentais, como cartas pessoais e entrevistas fictícias baseadas em declarações reais sobre alguns dos músicos mais representativos do começo do século XX, - Assis Valente, Cartola, Chiquinha Gonzaga, Luiz Gonzaga e Noel Rosa - quando o país, recém-independente, começava a firmar sua cultura particular. Nesses textos é possível, além de conhecer a biografia e a obra desses artistas, comparar o contexto histórico vivido por eles com a situação atual. O livro também traz uma vasta pesquisa dos ritmos musicais brasileiros, sua origem étnica, geográfica, as principais áreas de ocorrência no Brasil e como acontecem os desmembramentos e as derivações desses ritmos, valorizando desde a música erudita e orquestrada até os batuques de rua
Keywords: Música brasileira; Metrica e ritmo musical; Multiculturalismo; Cartas; Musica popular; Brazilian music